KONSEP AIR SEBAGAI SUMBER KEHIDUPAN DALAM AL-QUR’AN: Analisis Tafsir dan Perspektif Hidrologi - Muhammad Amin; M.Khidri Rahmad Dini; Muhammad Hafy Zaky; Ahmad Mujahid (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2025)
This study examines the concept of water as the source of life in the Qur'an through an interdisciplinary approach that integrates thematic exegesis with scientific perspectives from hydrology. The research focuses on identifying and analyzing Qur'anic verses that describe the stages of the hydrological cycle—including evaporation, condensation, precipitation, infiltration, and surface runoff—and correlating them with contemporary scientific understandings of the Earth's water systems. The findings reveal a significant correlation between the Qur'anic portrayal of water and the fundamental principles of hydrological science. This correlation not only demonstrates the coherence between divine revelation and empirical knowledge but also underscores the potential of religious texts to provide normative foundations for ecological ethics. The study is significant in that it positions the Qur'an as a valuable source for shaping sustainable water management paradigms while enriching thematic Qur'anic exegesis through a more contextual and environmentally responsive interpretive framework